Obesity influences the proteome of periodontal ligament tissues following periodontitis induction in rats - Lopes, Maria Eduarda Scordamaia [UNESP] (2022)
Background and Objectives: Many studies have been conducted to better understand the molecular mechanism involved with periodontitis progression. There has been growing interest in the potential impact of obesity on periodontitis onset and progression, but the mechanisms involved remain to be elucidated. The present study was designed to determine the impact of obesity on experimentally induced periodontitis in rats and identify novel pathways involved. Methods: Sixteen Holtzman rats were distributed into two groups (n = 8): ligature-induced periodontitis (P) and obesity plus ligature-induced periodontitis (OP). Obesity was induced by a high-fat diet for 70 days, whereas periodontitis was induced for 20 days, with a cotton thread placed around the upper first molars bilaterally. Alveolar bone loss was measured by microtomographic analysis and histologically by histometry on the hemimaxillae. The protein composition of the periodontal ligament was evaluated by proteomic analysis. Results: Data analysis (body weight, adipose tissue weight, and blood test) confirmed obesity induction, whereas bone loss was confirmed by micro-CT and histologic analyses. Proteome analysis from the periodontal ligament tissues (PDL) identified 819 proteins, 53 exclusive to the P group, 28 exclusive to the OP group, and 738 commonly expressed. Validation was performed by immunohistochemistry for selected proteins (spondin1, vinculin, and TRAP). Conclusion: Histologically, it was found that obesity did not significantly affect bone loss resulting from periodontitis. However, the present study's findings indicated that obesity affects the proteome of PDL submitted to experimental periodontitis, allowing for identifying potential targets for personalized approaches.